Quinoa Fiber and Quercetin Alter the Composition and Function of the Cecal Microbiome and Improve Brush Border Membrane Functionality and Morphology In-Vivo (Gallus gallus). (7th June 2021) - Agarwal, Nikita; Khen, Noa; Kolba, Nikolai; Tako, Elad
Abstract: Objectives: Assessment and comparison of the effects of various concentrations of soluble extracts of quinoa fiber ( Chenopodium quinoa Willd.) and quercetin-3-glucoside on the zinc and iron status, brush border membrane (BBM) functionality, intestinal morphology, and cecal bacterial populations in-vivo ( Gallus gallus ). Methods: The study utilized Gallus gallus intra-amniotic feeding, a clinically validated method to assess the effects of quinoa, quercetin, and control using seven groups (no injection, 18 Ω H2O, 5% inulin, 1% quercetin 3-glucoside, 2.5% quinoa fiber, 5% quinoa fiber, 1% quercetin 3-glucoside + 5% quinoa fiber). Upon hatch, the cecum, duodenum, pectoral muscle, liver, and blood samples were collected for the estimation of the relative abundance of the gut microbiome, mRNA gene expression Zn and Fe-related transporter proteins and brush border membrane functionality and morphology, glycogen, relative expression of lipid-related genes and hemoglobin levels, respectively. Results: The results demonstrated an increase ( P < 0.05) in villi height, weight, and surface area in the groups administered with quercetin, and a dose-dependent increase was observed with quinoa soluble fiber treatment. Additionally, an increase in ferroportin and duodenal cytochrome B (DcytB) was observed in the group injected with both quinoa and quercetin. Similarly, zinc transporter 7 (ZnT7) and sucrose-isomaltase (SI) gene expression was upregulated in this group. Further, the administration of quinoa soluble fiber altered the composition and function of the cecal microbiome. Conclusions: The evidence suggests that quinoa and quercetin have a synergistic effect, together they are found to improve BBM morphology and functionality, affect the intestinal microbiome, increase short-chain fatty acid production, and thereby improving mineral solubility. Quinoa fibers, a polyphenol-rich superfood, may help fight micronutrient deficiencies in target populations. Funding Sources: N/A.